Anamnesis and Absence in the Lord's Supper - Brawley, Robert L. (Biblical theology bulletin, 1990)
The view that the Lord's supper dynamically activates the presence of Christ governs the sacramentalism of the majority of Christians. Allegedly, its roots are sunk in a biblical idea of memorial. This article challenges that assumption and gives evidence that the dominant modem sacramentalism is a development beyond the canonical Second Testament. It also discusses themes of the absence of the risen Christ that run along with themes of presence in the Second Testament, relates those themes to the history of human suffering, and suggests that a modem consensus sacramentalism should be intentionally more inclusive.